Predictors of Incident and Persistent Neck/Shoulder Pain in Iranian Workers: A Cohort Study - Sadeghian, Farideh (Public Library of Science, 2013)
BACKGROUND: Pain in the neck and shoulder has been linked with various psychosocial risk factors, as well as with occupational physical activities. However, most studies to date have been cross-sectional, making it difficult to exclude reverse causation. Moreover, they have been carried out largely in northern Europe, and the relationship to psychosocial factors might be different in other cultural environments. METHODS: To explore causes of neck/shoulder pain, we carried out a longitudinal study in Iranian nurses and office workers. Participants (n  = 383) completed a baseline questionnaire about neck/shoulder pain in the past month and possible risk factors, and were again asked about pain 12 months later. Associations with pain at follow-up were explored by Poisson regression and summarised by prevalence rate ratios (PRRs). RESULTS: After adjustment for other risk factors, new pain at follow-up was more frequent in office workers than nurses (PRR 1.9, 95%CI 1.3–2.8), among those with worst mental health (PRR 1.8, 95%CI 1.0–3.0), in those who reported incentives from piecework or bonuses (PRR1.4, 95%CI 1.0–2.0), and in those reporting job dissatisfaction (PRR 1.5, 95%CI 1.0–2.1). The strongest predictor of pain persistence was somatising tendency. CONCLUSIONS: Our findings are consistent with a hazard of neck/shoulder pain from prolonged use of computer keyboards, although it is possible that the association is modified by health beliefs and expectations. They also indicate that the association of low mood with neck/shoulder pain extends to non-European populations, and is not entirely attributable to reverse causation. Psychosocial aspects of work appeared to have relatively weak impact.